DECREASE CLUBROOT DISEASE INTENSITY OF Brassica juncea ON Pb CONTAMINATED SOIL USING Paraserianthes falcataria THAT WAS INFECTED BY Mycorrhizal - E Kurniawan; Anton Muhibuddin; R R Kusuma (Journal of Environmental Engineering and Sustainable Technology, 2016)
Both, biotic and abiotic factor is the most important problem for agriculture in Indonesia. Biotic factor such as plant disease could decrease yield till more than 50%, while abiotic factor such as soil contamination could decrease yield till more than 30%. One of choice to overcome this problem is using bio-phytoremediation method. This method  combine remediation using plant (phytoremediation) and remediation using microbe (bio remediation). This study was aimed to determine the effects of bio-phytotemediation method using Paraserianthes falcataria which infected by mycorrhizal fungi to overcome Phytophthora brassicae, the main clubroot disease on Brassica juncea, in Pb contaminated soil. We also aimed to know the influence of the method to absorb soil Pb using Paraserianthes falcataria. The research was conducted in the Mycology Faculty of Agriculture, University of Brawijaya from March to October 2015. The research used Completely Randomized Design with 6 treatments and 4 replications. Parameter observation in this research were: 1) Intensity of clubroot disease; 2) Growth of B. juncea; 3) Population of mycorrhizal spores in soil,  4) Mycorrhizal infection inside plant cell; and 4) Pb content of soil and plant tissues. The results was showed  that mycorrhizal has significantly effects to decrease clubroot disease intensity. But, mycorrhizal has no significantly effect to the plant growth, including stem length and leaves number. The number of mycorrhizal spores in the soil after 35 days application was increases, and the percentage of infection in the roots of B. juncea and P. falcataria was fluctuated. The application of mycorrhizal can decrease Pb content in the soil and increase Pb content in P. falcataria.